If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 3(2a + -5) + -1(3a + 4) = 3a + -2(a + 2) Reorder the terms: 8 + 3(-5 + 2a) + -1(3a + 4) = 3a + -2(a + 2) 8 + (-5 * 3 + 2a * 3) + -1(3a + 4) = 3a + -2(a + 2) 8 + (-15 + 6a) + -1(3a + 4) = 3a + -2(a + 2) Reorder the terms: 8 + -15 + 6a + -1(4 + 3a) = 3a + -2(a + 2) 8 + -15 + 6a + (4 * -1 + 3a * -1) = 3a + -2(a + 2) 8 + -15 + 6a + (-4 + -3a) = 3a + -2(a + 2) Reorder the terms: 8 + -15 + -4 + 6a + -3a = 3a + -2(a + 2) Combine like terms: 8 + -15 = -7 -7 + -4 + 6a + -3a = 3a + -2(a + 2) Combine like terms: -7 + -4 = -11 -11 + 6a + -3a = 3a + -2(a + 2) Combine like terms: 6a + -3a = 3a -11 + 3a = 3a + -2(a + 2) Reorder the terms: -11 + 3a = 3a + -2(2 + a) -11 + 3a = 3a + (2 * -2 + a * -2) -11 + 3a = 3a + (-4 + -2a) Reorder the terms: -11 + 3a = -4 + 3a + -2a Combine like terms: 3a + -2a = 1a -11 + 3a = -4 + 1a Solving -11 + 3a = -4 + 1a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -11 + 3a + -1a = -4 + 1a + -1a Combine like terms: 3a + -1a = 2a -11 + 2a = -4 + 1a + -1a Combine like terms: 1a + -1a = 0 -11 + 2a = -4 + 0 -11 + 2a = -4 Add '11' to each side of the equation. -11 + 11 + 2a = -4 + 11 Combine like terms: -11 + 11 = 0 0 + 2a = -4 + 11 2a = -4 + 11 Combine like terms: -4 + 11 = 7 2a = 7 Divide each side by '2'. a = 3.5 Simplifying a = 3.5
| -19=7u+8(u+7) | | 21*4= | | log(7)(3x-5)=2+log(7)(x-6) | | 42x-18= | | 3/5y-8=-y | | 3/7(4-2)=2 | | 1.25x-3=30.5 | | 10x+5y=46 | | 4*(12/X)=7.03 | | 10x-9=8x+4 | | 1/4x^2-1/2x=6 | | 21X= | | 90+2b=99-b | | (4/3)3.14(9^3) | | cos2(x)=3/7 | | (12/x)*4=7.03 | | lnx=17 | | 14n=-8 | | -ax^2+2x+a=-2ax | | -11a+183=-5a+129 | | 5xi-5y+3i=2x+2yi-4 | | 8(5+5y)-2y(6+4)= | | (2x-5)+(3x-4)=-3 | | 5iz+3i=2z-4 | | i/7=4 | | 198-16= | | 15+x=15x | | 1/2+2/3= | | 17+k=9 | | xsquared+10x+10=0 | | cot^2(3x)=9 | | 109+89= |